2009
DOI: 10.1111/j.1369-1600.2009.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

BRIEF REPORT: Increased blood oxidative stress in amphetamine users

Abstract: Amphetamine derivatives have been shown to be a potential brain neurotoxin based on the production of free radicals that occurs after administration. The purpose of this study was to examine the lipid peroxidation and antioxidant enzymes in the blood of amphetamine users. The plasma lipid peroxidation was determined and reported as thiobarbituric acid reactive substance and was significantly increased (+21%), whereas the activities of the erythrocyte antioxidant enzymes glutathione peroxidase, catalase, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
6
8
1
Order By: Relevance
“…Our finding of enhanced lipid peroxidation is in agreement with previous reports that showed human METH users have higher MDA levels in the brain or in the blood …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding of enhanced lipid peroxidation is in agreement with previous reports that showed human METH users have higher MDA levels in the brain or in the blood …”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a persistent reduction of SOD activity suggests a compromised elimination of superoxide radicals in our subjects. This observation is compatible with another study that showed a lower erythrocyte SOD activity in the blood of amphetamine users . The post‐mortem study showed the SOD activity was instead elevated in the brains of METH abusers who tested positive for METH at autopsy .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, cocaine induced a 1.9-fold increase in locomotor activity after overexpression of α-synuclein in the NAc (Boyer and Dreyer, 2007). It is noteworthy that the neurotoxicity induced by the psychostimulants such as amphetamine are mediated by enhanced oxidative stress and these effects are abolished by melatonin (Govitrapong et al, 2010), a main secretory product of pineal gland. Interestingly, a recent report suggested that this melatonin effect is mediated by the reduction of the overexpression of α-synuclein induced by amphetamine (Sae-Ung et al, 2011).…”
Section: Dopamine Transporter and Neural Plasticitymentioning
confidence: 95%